A descriptive study to assess the knowledge and measures adopted by adults to prevent diabetes mellitus in selected villages of district sirmour, Himachal Pradesh - Khagta, Pratibha; Chakravarty, Sujana (International Journal of Nursing Research, 2023)
Diabetes mellitus is a chronic multisystem disease related to abnormal insulin production, impaired insulin utilization or both. Objectives of the study: The objectives of the study were to assess the level of knowledge and measures adopted by adults to prevent diabetes Mellitus, to find the association of knowledge score with selected variables and to find the correlation of knowledge score with measures adopted by adults to prevent diabetes mellitus. Methods: The Quantitative descriptive study was carried out in selected villages of district Sirmour, Himachal Pradesh. Using non-probability convenience sampling technique, 200 adults between the age group of 30-50 years were selected from selected areas. Data were collected using structured questionnaire regarding the prevention of diabetes mellitus and measures to prevent diabetes mellitus. Results: The results of the study revealed that 76% of the subjects had “poor knowledge”, 23 % had “average knowledge” while only 1% had “good knowledge”. Findings of measures adopted depict that majority of respondents adopt average measures (58.5%) and 38.5 % had poor measures while only 3% had good measures. diabetes mellitus. Conclusion: Current study reflected the poor knowledge about diabetes in rural India. This indicates that the population needs to be taught about diabetes in early care settings.